Photoinhibition of Cyanobacteria and its Application in Cultural Heritage Conservation. (10th December 2013) - Hsieh, Paul; Pedersen, Jens Z.; Bruno, Laura
Abstract Light has bilateral effects on phototrophic organisms. As cyanobacteria in Roman hypogea are long acclimatized to dim environment, moderate intensity of illumination can be used to alleviate biodeterioration problems on the stone substrata. Moderate intensity of light inactivates cyanobacteria by causing photoinhibition, photobleaching and photodamage to the cells. The effectiveness of light depends not only on its intensity but also on the composition and pigmentation of the component cyanobacteria in the biofilms. Red light is the most effective for the species rich in phycocyanin and allophycocyanin, such as Leptolyngbya sp. and Scytonema julianum, whereas green light is effective to inhibit the species rich in phycoerythrin, like Oculatella subterranea. White light is effective to control the grayish and the black cyanobacteria, such as Symphyonemopsis sp. and Eucapsis sp. abundant in all of these pigments. Blue light is the least effective. 150 μmol photons m−2 s−1 of blue light cannot cause biofilm damage while the same intensity of red, green or white irradiation for 14 days can severely damage the cyanobacterial cells in the biofilms due to ROS formation. Electron spin resonance spectroscopy detected the formation of radicals in different cyanobacterial cellular extracts exposed to 80 μmol photons m−2 s−1 of light.